The English system for ensuring health care and health monitoring of looked after children. (25th March 2018) - Simkiss, Doug; Jainer, Renu
Abstract : The article describes the history of the current system of health care and monitoring for looked after children in England, the reasons why looked after children have a dedicated service and the details of current provision. National guidance from the Department of Health and Department for Education, the Chief Medical Officer for England, the National Institute for Health and Care Excellence and the Royal College of Paediatrics is explained. We outline some strengths and limitations of the current system. There are many similarities with the system in Wales, Scotland and North Ireland, but different legislative frameworks and some important differences in process, so this article focuses specifically on the system in England.